Big Data Analysis: A Review (International Journal of Engineering and Computer Science, 2017)
Name defines its size only besides, broader dimensions and scopes define Big Data in most appropriate terms. This paper attempts to provide a consolidate knowledge of Big Data by covering its peripheral definitions and benefits. With the advancement in technologies and enhanced scale of Internet of Things, millions of people get the avail services and customize them accordingly. Besides, there emerge needs for analyzing the information gained, arranging the data and retrieving useful information. Here Big Data and its opportunities can be visualized. Data analysis is the root and essential step for retrieving Big Data and their proper processing. This paper provides fundamental and ground level knowledge about Big Data, its beneficial phases, challenges, and its essential role for creating vast positive differences in many fields from social networking to e-commerce to medical sciences and in many other scenarios. Many researches are made under this title showing its worth and scope besides, there are many other researchers indulged in developing methods and processes to more and more effective computation of Big Data. This review thesis gives away a comprised and multi-defined prospect of Big Data covering all its related knowledge and concepts. Traditional aspects of analysis of Big Data is also covered along with the latest technology discussion of Hadoop and further its limitations. This paper also concludes and reinforces the desired necessity for to innovate new tools and mechanisms for relevant computation and analysis of structured as well as unstructured Big Data. Therefore, for deceiving the complexity and incrementing the opportunities of Big Data in order to visualize enormous useful integrated phase for advancement, this paper attempts to map primarily bottom up approach to learn and understand Big Data in more precise manner.